2010
DOI: 10.1088/0953-4075/43/21/215503
|View full text |Cite
|
Sign up to set email alerts
|

Realization of a negative refractive index in a three-level Λ system via spontaneously generated coherence

Abstract: A new scheme to realize simultaneous negative permittivity and permeability in a three-level closed Λ system with incoherent pumping via spontaneously generated coherence has been presented. We have shown that the negative refractive index can be realized in a heteronuclear molecule such as LiH. The negative refractive index can be achieved in a band of frequency range. The position and the band of the frequency region of negative refraction can be manipulated by controlling the incoherent pump rate. We achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The existence of SGC effect depends on the non-orthogonality of the two dipole transition moments, which can be obtained from the mixing of the levels arising from internal fields such as, for example, the superposition of singlet and triplet states due to spin-orbit coupling in sodium dimers [36] or by external fields, as shown previously [37][38][39]. In our previous work, we have also shown how SGC in molecules can be invoked by an external field [34,40].…”
Section: Resultsmentioning
confidence: 65%
“…The existence of SGC effect depends on the non-orthogonality of the two dipole transition moments, which can be obtained from the mixing of the levels arising from internal fields such as, for example, the superposition of singlet and triplet states due to spin-orbit coupling in sodium dimers [36] or by external fields, as shown previously [37][38][39]. In our previous work, we have also shown how SGC in molecules can be invoked by an external field [34,40].…”
Section: Resultsmentioning
confidence: 65%
“…Since then, several other studies on negative refractive index have been carried out in four- [21][22][23][24][25][26] and five- [27] level atomic systems that can be easily generated negative refractive index in different frequency bands. Recently, some authors have used the SGC effect to achieve negative refractive index with significantly reduced absorption and to control the frequency band of negative refractive index according to laser parameters and quantum interference parameter [28][29][30]. Under SGC condition, the refractive index can be switched from positive to negative or vice versa by varying the relative phase of laser fields and the strength of SGC.…”
Section: Introductionmentioning
confidence: 99%
“…Later Shen et al [35] suggested a scheme based on a quantum mechanical approach to realize negative permeability in a à system and proposed that if one mixes the negative permeability vapour with Agarwal et al's negative permittivity vapour [34], the produced mixed atomic vapour may exhibit left-handedness for the probe light. Very recently we have proposed a new scheme to realize simultaneous negative permittivity and permeability in a three-level closed system neglecting the local field effect [36,37].…”
Section: Introductionmentioning
confidence: 99%